Student Learning Styles in The Industrial Revolution 4.0 - Febri Yanti; Lufri Lufri; Yuni Ahda (Postgraduate, University of Mataram, 2021)
The industrial revolution 4.0 in the field of education provides convenience in learning methods and processes. Internet-based technology makes it easier for students to learn independently, quickly in providing feedback, and freely choose material from library sources from anywhere. As a result, student learning styles change along with the development of internet-based technology. In the coursework, students can read and combine various writings from several sources, and in-class when students present assignments of learning materials that have been read so that they are easily understood by other students. Likewise, in completing paper assignments from lecturers, students can read various papers given by many lecturers. This happens because of the students' understanding of the assignments given by the lecturer. The purpose of this study was to identify the learning styles of students of the Biology Education Study Program, STKIP PGRI Sumatera Barat on the development of internet-based technology in the industrial revolution 4.0. This type of research is descriptive and the approach used is quantitative. The results of this study indicate that the learning style of students of the Biology Education Study Program STKIP PGRI Sumatera Barat, Padang, West Sumatra tends to be visual, namely 60.3%. The presence of internet technology and its use in an educational institution is a medium or source of learning that can be utilized by students